Konsep Pendidikan Karakter Islam Moderat dalam Akhlaq Ar-Rasul Shollallahu Alaihi Wa Sallama lil Athfal Karya Syaikh Mahmud Al-Mishri - Achmad; Muhammad Shohib (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the concept of moderate Islamic character education presented in Akhlaq Ar-Rasul Shollallahu Alaihi Wa Sallama Lil Athfal by Sheikh Mahmud Al-Mishri and explores its relevance for shaping the moral character of young people in the digital era. Using library research and a descriptive qualitative approach, the study analyzes the core values of moral moderation emphasized by Al-Mishri. The findings reveal that the principles of tawassuth (middle path), i‘tidāl (proportionality), and tawāzun (balance) serve as the foundation for developing well-balanced character traits such as trustworthiness, honesty, disciplined courage, patience, generosity, and social responsibility. These values are highly relevant for addressing moral decline among youth and for fostering a proportional religious understanding and constructive social behavior. The study underscores the importance of strengthening character education based on Islamic moderation to cultivate morally grounded and adaptive young generations capable of responding to contemporary challenges.